Digital-Based Media Flashcards in Primary School English Learning, is it Effective? - Ni Nyoman, Trianaswari Predani; Anak Agung, Gede Agung; Luh, Ayu Tirtayani (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
Nowdays effective learning media is very needed, such as Digital-Based Flashcards for grade V elementary school English lesson content. Therefore, this study aims to develop an effective Digital-Based Flashcard learning media for grade V elementary school English lesson content. This research is development research (Research and Development) by adapting the ADDIE development model. Data collection was carried out using instruments in the form of questionnaires and learning outcomes tests. Media validity data is sourced from one design expert, one learning media expert, one instructional design expert, and one elementary school English learning content expert. Media practicality data were sourced from three students for individual trials and nine for small group trials. The data analysis process is carried out using qualitative and quantitative approaches. The development results show that the digital-based Flashcards learning media on the English lesson content for grade V elementary school is as follows. (1) be declared valid based on the results of the assessment of design experts, media expert, and content expert. (2) is declared practical based on highly qualified individual users, trials of small-group users and product effectiveness test using the t-test technique which obtain significance level. This research implies that digital-based flashcard learning media is needed to increase the content of English lessons for grade V elementary schools.